Nurturing Social Intelligence Through AuthenticSocial Experiences: A Study Of Muslim Gifted And Talented Students - Nurhannah Syifa’ Binti Khairuddin; Nur Alya Binti Basri; Amnah Zanariah Binti Abd Razak; Amirah Binti Zainun; Nur Fazidah Asmuje@Asmuzi (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025